Case Report: Prenatal neurological injury in a neonate with pyruvate carboxylase deficiency type B - Xue, Mei (Frontiers in Endocrinology, 2023)
Background Pyruvate carboxylase (PC) is a key enzyme for gluconeogenesis. PC deficiency (PCD) is an extremely rare autosomal recessive metabolic disease and is divided into three types. Type B PCD is clinically featured by lactic acidosis, hyperammonemia, hypercitrullinemia, hypotonia, abnormal movement, and seizures. Case presentation Here, we report the first case of type B PCD in China, presenting with intractable lactic acidosis shortly after birth. A compound heterozygous mutation in the PC gene was identified by whole-exome sequencing, NM_001040716.2: c.1154_1155del and c.152G>A, which were inherited from her asymptomatic parents, respectively. Furthermore, prenatal neuroradiological presentations including widened posterior horns of lateral ventricles, huge subependymal cysts, and increased biparietal diameter and head circumference were concerned. Symptomatic treatment was taken and the infant died at 26 days. Conclusion To our knowledge, this is the minimum gestational age (22w5d) that’s when the prenatal onset of the neuroradiologic phenotype of PCD was observed. PCD has a poor prognosis and lacks an effective treatment, so this paper is shared to highlight the importance of PCD prenatal diagnosis in the absence of family history.